Epidemio-entomological Study of Japanesse Encephalitis in Bhaktapur District, Nepal - Shrestha, Monica; Gupta, Ranjana; Gautam, Ishan (Journal of Institute of Science and Technology, 2015)
A descriptive cross-sectional questionnaire survey on Japanese encephalitis was conducted in Bhaktapur district. Mosquitoes were collected for six months by means of dark activated rechargeable CDC light trap. Out of 884 mosquitoe individuals collected, 73.41 percent were Culex species. The highest numbers of mosquitoes were collected in July and August. There was no significant variation in Culex vectors abundance during six months in three study sites Tathali, Bode and Bhelukhel. Significant correlation was found between level of knowledge and attitude towards JE prevention. Fair level of practice towards JE prevention but having no good attitude shows that though people are supportive towards JE control. Journal of Institute of Science and Technology, 2015, 20(1): 112-118